Operational Eciency Optimization of a Peruvian Bank Branches using Data Envelopment Analysis - Clemente Moquillaza, Luis (2019)
Data envelopment analysis is a non-parametric practical method to compute eﬃciency on decision making units. The present work applies DEA on then branch network of one of the most important peruvian banks with a Lingo optimization model and a Microsoft Excel spreadsheet. The problem is solved under two approaches (ﬁnancial/management and selling) in order to compute both global and technical eﬃciency of each individual branch. Additionally, a ranking system (based on average eﬃciency, time-windows analysis and benchmark-solution recurrence) is proposed as a management tool for the direction teams.